Istilah-istilah dalam Budidaya Tanaman Padi di Desa Banjarsari, Kabupaten Cilacap, Jawa Tengah - Suyanto Suyanto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This paper aims to (1) describe the terms used in the rice cultivation process and (2) explain the lexical and cultural meaning of terms in the process of rice cultivation. This study uses the language relativism approach. Language relativism assumes that the meaning of the lexicon of each language or dialect of a language is relative, depending on the location and time. The research locus chose Banjarsari Village, a village on the east end of Cilacap Regency, Central Java. Data collection uses narrative and observations methods. The sources of this study were seven farmers in Banjarsari Village. Data analysis through five stages, namely data reduction, data display, data verification, theoretical interpretation and meaning, and conclusion results. The results of the study show that the terms in rice cultivation include 17 terms and two terms postharvest activity (mepe and slip). Seventeen of these terms consist of 5 terms in the nursery stage, four terms in the land preparation stage, five terms of the treatment phase, and three terms at the harvest stage.